Baastrup's Disease as a Rare Cause of Cauda Equina Syndrome: A Case Report. Issue 2 (2nd April 2022) - Egu, Chinedu Brian; D'Aquino, Daniel; Mcculloch, Thomas; Pasku, Dritan
Abstract : Case: "Baastrup's disease" is a relatively common anatomical condition, controversially recognized as a possible cause of back pain but frequently missed by clinicians of different specialties. We present a rare case of Baastrup's disease causing compression to the cauda equina nerves due to the formation of a large pseudotumoral epidural mass. The patient underwent a successful surgical decompression with remarkable improvement in her neurological presentation. The histopathological findings consisted of increased collagen deposition and chondroid metaplasia. Conclusion: Clinicians should be aware of possible cauda equina syndrome in rare cases of Baastrup's disease due to pseudotumoral mass compression in the lumbar spine.